Gerakan Percepatan Penganekaragaman Konsumsi Pangan (P2KP) Untuk Antisipasi Dampak Perubahan Iklim Pada Sektor Pertanian - Lolita Endang Susilowati; Uyek Malik Yakop; Bambang Hari Kusumo (Universitas Mataram, 2020)
Climate change causes changes in rainfall patterns that is high intensity rain in a short duration. This situation could threaten the agricultural sector which impacts on national food security and food fulfillment for each household. Therefore, it is necessary to introduce an effective strategy to meet household food needs through the P2KP movement in dealing with the threat of climate change. This community service aims to: (1) providing an understanding of climate change and its impact on the food agriculture sector to the community; (2) socializing the